MANAJEMEN PEMBINAAN ANAK USIA 10-12 TAHUN PADA KLUB VOLI TUNAS MUDA KABUPATEN BATANGHARI - Nabila Sapitri; Palmizal A; Ceppy Pradana Putra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the management of coaching for children aged 10–12 years at the Tunas Muda Volleyball Club, Batanghari Regency. The research employed a descriptive qualitative approach to obtain an in-depth understanding of the implementation of coaching management, including planning, organizing, implementation, and evaluation. Data were collected through observations, interviews, and documentation involving club administrators, coaches, and parents of athletes selected using purposive sampling techniques. Data analysis was conducted using thematic analysis assisted by NVivo 12 Plus through coding, visualization, and interpretation of research findings. The results showed that the coaching management at Tunas Muda Volleyball Club had generally been implemented systematically and reflected the application of management functions. The planning process was carried out through structured and gradual training programs adjusted to the characteristics of children aged 10–12 years. Organizing activities involved clear role distribution among administrators, coaches, and parents. The implementation of coaching emphasized demonstration methods, game-based activities, and varied exercises to maintain children’s motivation and participation. Evaluation was conducted regularly through direct observation and monitoring of children’s technical skills, discipline, and physical development. Supporting factors included structured training programs, active coach involvement, and parental support, while inhibiting factors involved limited facilities, inconsistent athlete attendance, and the absence of standardized evaluation instruments. Therefore, strengthening cooperation among administrators, coaches, and parents, as well as improving facilities and evaluation systems, are necessary to optimize the sustainability and effectiveness of early-age volleyball coaching programs.